Hög sjukfrånvaro bland yrkesarbetare inom en kommunal förvaltning i Luleå : En kvantitativ undersökning med fokus på arbetslivsrelaterade faktorer - Lupescu, Georgiana (2015)
The purpose of this study was to identify and analyze some of the factors that could explain the fact that the level of sickness absenteeism within the department that performs various kinds of professional work in the municipal administration of Luleå is constantly above the target value that is four percent. The main hypothesis was that the work environment has a great significance for these skilled workers health. The correlation between the psychosocial work environment and the employees’ health, the correlation between the physical environment and the level of sickness absenteeism within the department, and the correlation between the performed housework and these patterns of sickness absenteeism were analyzed in order to answer the purpose of the study. Quantitative empirical data collection methods were used based on a questionnaire that was distributed within the department. The quantitative methods that were selected suited well to the study, as all skilled workers within this department were given the opportunity to participate in the survey, which was an advantage for the generalization of the study results. In addition to the survey, it was also required reading of official reports found on the Internet, as well as books and scientific papers found at the university library.Based on the results of the study, it clearly emerges that the psychosocial work environment plays an important role for these employees’ health. There is an unbalance between the workload, the capacity to influence the work process and the difficulty of the tasks, which affects the skilled workers mental health negatively because of their low control over the work. All these aspects generate a high level of stress among the employees and the male skilled workers are much more affected in compare to the rest of the personnel. Women have mostly problems in getting support from their colleagues or foremen, which affects both the way they involve themselves in the work process and their feelings before and during the spell of work. ...